Precursor Mediated Synthesis of Nanostructured Silicas: From Precursor-Surfactant Ion Pairs to Structured Materials - Hesemann, Peter (Materials (Basel), 2014)
The synthesis of nanostructured anionic-surfactant-templated mesoporous silica (AMS) recently appeared as a new strategy for the formation of nanostructured silica based materials. This method is based on the use of anionic surfactants together with a co-structure-directing agent (CSDA), mostly a silylated ammonium precursor. The presence of this CSDA is necessary in order to create ionic interactions between template and silica forming phases and to ensure sufficient affinity between the two phases. This synthetic strategy was for the first time applied in view of the synthesis of surface functionalized silica bearing ammonium groups and was then extended on the formation of materials functionalized with anionic carboxylate and bifunctional amine-carboxylate groups. In the field of silica hybrid materials, the “anionic templating” strategy has recently been applied for the synthesis of silica hybrid materials from cationic precursors. Starting from di- or oligosilylated imidazolium and ammonium precursors, only template directed hydrolysis-polycondensation reactions involving complementary anionic surfactants allowed accessing structured ionosilica hybrid materials. The mechanistic particularity of this approach resides in the formation of precursor-surfactant ion pairs in the hydrolysis-polycondensation mixture. This review gives a systematic overview over the various types of materials accessed from this cooperative ionic templating approach and highlights the high potential of this original strategy for the formation of nanostructured silica based materials which appears as a complementary strategy to conventional soft templating approaches.